2019
DOI: 10.2478/macvetrev-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistomorphometric Changes of The Pituitary Gonadotropic Cells After Testosterone Application in a Rat Model of the Andropause

Abstract: Andropause, the culminating phase of male ageing, is characterized by deregulation of the hypothalamic-pituitarygonadal axis and low circulating free testosterone. The aim of this study was to investigate the immunohistomorphometric characteristics of the pituitary gonadotropic i.e. follicle-stimulating hormone (FSH) and the luteinizing hormone (LH) producing cells after testosterone application in a rat model of the andropause. Middle-aged Wistar rats were divided into orchidectomized (ORX; n=8) and testoster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…These effects of the anabolic steroid administration are caused by the negative feedback mechanism. Similar findings were reported by Ristić et al (2019). They showed that testosterone administration decreased volume density and also optical density of pituitary gonadotropic cells in orhidectomized rats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These effects of the anabolic steroid administration are caused by the negative feedback mechanism. Similar findings were reported by Ristić et al (2019). They showed that testosterone administration decreased volume density and also optical density of pituitary gonadotropic cells in orhidectomized rats.…”
Section: Discussionsupporting
confidence: 92%
“…They showed that testosterone administration decreased volume density and also optical density of pituitary gonadotropic cells in orhidectomized rats. Furthermore, they detected that the increased levels of testosterone in orhidectomized rats led to a decrease of size and number of gonadotropic cells in the pituitary gland, which is, in our opinion, direct confirmation that the sex hormone had a crucial influence on both function and morphometric parameters of gonadotropic cells by the mechanism of negative feedback (Ristić et al, 2019). In our study, serum levels of LH and FSH hormones were decreased after treatment with nandrolone decanoate alone or combined with swimming training.…”
Section: Discussionmentioning
confidence: 53%